A WebGIS-Based Location Analysis System for Disaster Mitigation in Bitung City Using Ray Casting and Haversine Formula - Romeo Fernando Mikhael Dendeng; Kristofel Santa; Sondy C. Kumajas (Sinkron : jurnal dan penelitian teknik informatika, 2026)
Indonesia is highly vulnerable to multi-hazard natural disasters, and Kota Bitung specifically faces high risks due to its geographical contours. Currently, the dissemination of disaster information by the Regional Disaster Management Agency (BPBD) relies heavily on conventional static maps. Most existing disaster WebGIS platforms focus merely on static visualization and lack an integrated system capable of instantly analyzing a user's coordinate status against multi-hazard spatial polygons while simultaneously providing location-based evacuation routing. To address this gap, this research aims to design and develop a responsive WebGIS that allows users to independently detect their risk status and logically find the nearest evacuation route. The system development utilizes the Rapid Application Development (RAD) method. The core engine integrates the Ray Casting algorithm to solve the Point-in-Polygon problem against disaster zone boundaries, and the Haversine Formula to calculate the nearest available evacuation point. Based on comprehensive evaluations, including accuracy testing, spatial distance validation, and 11 distinct black-box testing scenarios, the system successfully processed GPS-based coordinate inputs, handled polygon boundary edge-cases, and generated evacuation routes using the OpenSource Routing Machine (OSRM). Ultimately, the proposed system provides a functional prototype for location-based disaster risk analysis and evacuation point recommendation, serving as a foundational interactive instrument to support emergency preparedness in Kota Bitung.